Small-χ structure functions and heavy flavour production - Catani, S; Ciafaloni, M; Hautmann, F (1991)
The use of the kt-factorization theorem to compute high energy cross sections in resummed perturbation theory is reviewed. The results for heavy flavour photoproduction at small χ are discussed in detail. We show that the resummation of the leading terms in the perturbative series gives large correction factors with respect to lowest order calculations. © 1990.